New Trends and Challenges in Precision and Digital Agriculture - Gniewko Niedbała; Magdalena Piekutowska; Patryk Hara (Agronomy, 2023)
Real change is needed in the agricultural sector to meet the challenges of the 21st century in terms of humanity’s food needs [...]